Comparative performance evaluation of Frieswal bulls in organized farms and farmers' herds - KUMAR, SUSHIL; ALEX, RANI; SINGH, UMESH; KUMAR, ARUN; DAS, A K (The Indian Journal of Animal Sciences, 2015)
The present study was focused to determine the genetic worth of Frieswal bulls under farm and field conditions and to assess their rankings in both production systems. The first lactation records of 3,582 crossbred cows maintained at Military Farms (2,851) and in farmer’s herds (731) which were daughters of 32 bulls and calved during 14 years from 1998 to 2011 were used in the present study. The average first lactation milk yield in crossbred cows was 2,886.60± 32.78 and 2,666.17± 71.21 kg at Military Farms and field units respectively. Year of calving in farms and season of calving in field had significant effect on the first lactation milk yield. Herd/location of the farm was found significant in both conditions. Breeding value estimates of the sires ranged from 2,824.28 to 2,919.19 and from 2,650.41 to 2,758.81 kg under farm and field conditions respectively. Eight bulls (25%) under farm conditions and 27 bulls (84%) under field conditions exceeded their breeding value over the herd average. The low and nonsignificant product moment correlation (–0.261) and rank correlation (–0.296) between breeding values of bulls under farm and field conditions revealed that bulls with higher ranks for milk production under farm conditions did not retain their superiority in field conditions. Therefore top ranked Frieswal bulls tested under farm conditions cannot be recommended for their use as proven bulls in field conditions. The breeding program should also be optimized to respond to multiple environment requirements, as re-ranking of bulls occurred in the 2 environment conditions.